STRATEGI MANAJEMEN HUMAS DALAM MENJALIN KERJA SAMA DI SMKN - Ahmad Muslim; Lukmanul Hakim; Candra Adi Saputra (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The focus of this research is 1) public relations management strategies implemented at SMKN (Vocational High Schools). 2) form of cooperation between SMKN and the community. 3) the impact of implementing public relations management in establishing cooperation with the community. Problems identified include a lack of understanding and awareness of the importance of public relations management among school staff or administrators, a lack of planned and directed strategies in managing collaboration with external parties, obstacles in effective communication and relationships between schools and various related parties such as government agencies, companies, or the wider community. This research uses a qualitative approach. Data collection uses observation, interviews and documentation methods. The results of this research include: 1) The public relations management strategy implemented at SMKN, namely the use of social media, websites and mainstream media to increase the school's visibility, as well as involve the community in various school activities and programs. 2) Forms of cooperation between SMKN and the community include collaboration with government institutions, the business world and industry, as well as involving the community in social activities, skills training and community activities. This collaboration provides reciprocal benefits for schools and communities, increasing educational and training opportunities, and strengthening community involvement in school development. 3) The impact of implementing public relations management in collaboration with the community at SMKN has had a significant positive impact.